2004
DOI: 10.1073/pnas.0403249101
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Toll-like receptor 4 or myeloid differentiation factor 88 reduces atherosclerosis and alters plaque phenotype in mice deficient in apolipoprotein E

Abstract: Toll-like receptors (TLRs) and the downstream adaptor molecule myeloid differentiation factor 88 (MyD88) play an essential role in the innate immune responses. Here, we demonstrate that genetic deficiency of TLR4 or MyD88 is associated with a significant reduction of aortic plaque areas in atherosclerosis-prone apolipoprotein E-deficient mice, despite persistent hypercholesterolemia, implying an important role for the innate immune system in atherogenesis. Apolipoprotein E-deficient mice that also lacked TLR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
737
1
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 937 publications
(782 citation statements)
references
References 58 publications
32
737
1
12
Order By: Relevance
“…[25][26][27][28] Given the involvement of NFkB signaling in atherosclerosis, LPS was used to activate it and stimulate the production of NFkBdependent pro-inflammatory cytokines. 29,30 Indeed, LPS caused a sustained activation of p65 in THP-1 macrophages ( Fig.…”
Section: Establishing Rap1 Knockdown In Thp-1 Macrophagesmentioning
confidence: 99%
“…[25][26][27][28] Given the involvement of NFkB signaling in atherosclerosis, LPS was used to activate it and stimulate the production of NFkBdependent pro-inflammatory cytokines. 29,30 Indeed, LPS caused a sustained activation of p65 in THP-1 macrophages ( Fig.…”
Section: Establishing Rap1 Knockdown In Thp-1 Macrophagesmentioning
confidence: 99%
“…Circulating monocytes overexpress TLR4 during acute coronary syndrome, 12 and TLR4 is expressed in atherosclerotic plaques. 13,14 Apolipoprotein E knockout mice lacking TLR4 develop reduced atherosclerotic lesions, 15 and a TLR4 genetic variation is associated with diminished risk of atherosclerosis. 16 Apart from microbial molecules such as lipopolysaccharides, autoantigens found in the plaque environment are also candidates for TLR4-dependent activation of APCs.…”
Section: Clinical Perspective P 2052mentioning
confidence: 99%
“…[19][20][21] The TLR4 signaling activates mitogen-activated protein kinases and production of interferon-gamma-inducible protein 10 (IP-10), in turn activating protein kinase C (PKC) and finally resulting in the translocation of NF-kB. [22][23][24] Recent studies have revealed that the TLR4 signaling plays a central role in atherosclerosis, [25][26][27] thus providing an important link between inflammation, innate immunity and atherosclerosis. Although PPARg agonists exert anti-inflammatory and antiarteriosclerotic actions in the cardiovascular system, the exact mechanisms, whereby rosiglitazone affects Ang II-mediated inflammatory responses, and the TLR4-dependent signaling pathway involved are largely unknown.…”
mentioning
confidence: 99%